2015
DOI: 10.1038/nn.3923
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-evoked negative symptoms require AMPA receptor trafficking in the lateral habenula

Abstract: Addictive substances mediate positive and negative states promoting persistent drug use. However, substrates for aversive effects of drugs remain elusive. We found that, in mouse lateral habenula (LHb) neurons targeting the rostromedial tegmental nucleus, cocaine enhanced glutamatergic transmission, reduced K+ currents and increased excitability. GluA1 trafficking in LHb was instrumental for these cocaine-evoked modifications and drug-driven aversive behaviors. Altogether, our results suggest that long-lasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
109
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(120 citation statements)
references
References 20 publications
8
109
1
2
Order By: Relevance
“…Implication of the tVTA, which receives afferents from the LHb (Balcita-Pedicino et al, 2011;Jhou et al, 2009a;Kaufling et al, 2009) and controls dopamine cell activity (Bourdy et al, 2014;Jalabert et al, 2011;Jhou et al, 2009b;Matsui and Williams, 2011), has been described in active, passive, and conditioned avoidance behaviors and in the processing of aversive information (Jhou et al, 2009b(Jhou et al, , 2013Lammel et al, 2012;Meye et al, 2015;Stamatakis and Stuber, 2012). To date, however, the most striking Fos responses in this structure were observed with psychostimulants (Cornish et al, 2012;Jhou et al, 2009aJhou et al, , 2013Geisler et al, 2008;Kaufling et al, 2010b;Lecca et al, 2011;Perrotti et al, 2005;Zahm et al, 2010) (see Supplementary Table S3 and Supplementary Data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implication of the tVTA, which receives afferents from the LHb (Balcita-Pedicino et al, 2011;Jhou et al, 2009a;Kaufling et al, 2009) and controls dopamine cell activity (Bourdy et al, 2014;Jalabert et al, 2011;Jhou et al, 2009b;Matsui and Williams, 2011), has been described in active, passive, and conditioned avoidance behaviors and in the processing of aversive information (Jhou et al, 2009b(Jhou et al, , 2013Lammel et al, 2012;Meye et al, 2015;Stamatakis and Stuber, 2012). To date, however, the most striking Fos responses in this structure were observed with psychostimulants (Cornish et al, 2012;Jhou et al, 2009aJhou et al, , 2013Geisler et al, 2008;Kaufling et al, 2010b;Lecca et al, 2011;Perrotti et al, 2005;Zahm et al, 2010) (see Supplementary Table S3 and Supplementary Data).…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, ablation of the tVTA inhibits fear-conditioned freezing, passive response to a predator odor, and anxiety-like behavior in an elevated plus maze (Jhou et al, 2009b). It also suppresses cocaine-induced avoidance behavior in a runway operant paradigm (Jhou et al, 2013), and cocaine excitation of LHb-tVTA neurons contributes to cocaineinduced depressive-like behaviors (Meye et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the changes were dependent on GluA1 subunitcontaining AMPAR trafficking in these neurons. Its inhibition by virally expressed GluA1 C-terminal peptide resulted in a reduction in depression-like behaviors on withdrawal and in persistent neuronal changes in the LHb (Meye et al, 2015). Therefore, these studies implicate the LHb-rmTg-VTA axis in the negative symptoms associated with cocaine withdrawal.…”
Section: Drug-induced Neuroplasticitymentioning
confidence: 75%
“…1). By using an ex vivo preparation similar to earlier studies in Drug-Induced Neuroplasticity the VTA and NAc (discussed earlier), it was recently shown that two prior in vivo, noncontingent doses of cocaine selectively enhance glutamatergic transmission onto LHb neurons projecting to the rmTg (as well as increasing excitability of these neurons by reducing K + currents) (Meye et al, 2013(Meye et al, , 2015. These changes persisted for 1 week, whereas a chronic cocaine regimen (5 noncontingent doses) results in similar persistent changes for 2 weeks (at which point, depressive-like "withdrawal" behaviors were observed).…”
Section: Drug-induced Neuroplasticitymentioning
confidence: 99%
“…[7,10] (Figures 1B, 1C). La tVTA est également l'efférence 4 principale de l'habénula latérale 5 [6,7], qui contribue vraisemblablement aux effets aversifs de la cocaïne [11] et à l'état de type dépressif accompagnant son sevrage [12,13] ( §). La mise en évidence du rôle de la tVTA dans la réponse dopaminergique aux opiacés a aussi constitué une avancée majeure de ces dernières années [4].…”
unclassified